PO.8.164 Melanoderma induced by long-term use of hydoxychloroquine in SLE. (27th September 2022) - Kella, A; Derbal, F; Bouziani, N; Belabbas, A; Derder, M; Hakem, D
Abstract : Introduction: Hydroxychloroquine (HC) remains a standard treatment in many systemic diseases, including systemic lupus erythematosus (SLE), rheumatoid arthritis and many others, but these multiple side effects are often overlooked. The best known of its adverse effects are retinitis pigmentosa, digestive disorders and disturbances in liver function tests, unlike the mucocutaneous effects. Objective: To draw attention to melanoderma as a mucocutaneous side effect of long -term use of HC. Observation: We report the case 55 years old woman witch was diagnosed and monitored for SLE 15 yeras ago. She is currently being treated with HC 400mg/d with prednisone at 10mg/d. This patiente was in prolonged remission from her disease and declares that she is satisfied with her treatment until diffuse melanodermal lesions appear on her body, bothersome and above all worrying the patient. These melanodermal spots are located on the upper and lower extremities, abdomen and oral cavity. Discussion: After ruling out all of the other causes of melanoderma, in particular slow adrenal insufficiency and paraneoplastic syndrome, and considering the long-term intake of HC likely to cause such a side effect, we confirmed the iatrogenic causality link. The patiente was informed and the causal drug was stopped with narrow monitoring of the lupus disease. The prolonged duration of drug exposure could ensure a sufficient cumulative dose allowing for a therapeutic window. The reintroduction of HC was estimated possible after total disappearance of the melanoderma. However, this must be gradual and as late as possible. Conclusion: In addition to the known side effects of HC, melanoderma is not uncommon and must be taken into consideration without disturbing the management of the disease treated by this molecule recognized by antiinflammatory, immunomodulatory and antithrombogenic actions.